The Effect of Body Mass Index on Brain Volume and Cognitive Function in Relapsing–Remitting Multiple sclerosis: A CombiRx Secondary Analysis. (2nd November 2021) - Ben-Zacharia, Aliza Bitton; Janal, Malvin N.; Brody, Abraham A.; Wolinsky, Jerry; Lublin, Fred; Cutter, Gary
Background: Multiple sclerosis (MS) is an autoimmune disease leading to physical, emotional and cognitive disability. High body mass index (BMI) may impact cognitive function and brain volume in MS. Yet, there is paucity of evidence addressing the impact of BMI on cognitive function and brain volume in MS. Objectives: The purpose of this study was to examine the effects of BMI on normal appearing brain volume and cognitive function in patients with relapsing–remitting MS. Methods: A secondary data analysis of the NIH CombiRx study was conducted. Multivariate regression and mixed model analyses were executed to analyze the effect of BMI on brain volume and cognitive function. Results: The mean baseline age of the 768 participants was 38.2(SD = 9.4) years. 73% were female and 88.8% were Caucasian. The mean BMI was 28.8 kg/m 2 (SD = 6.7). The multivariate regression and mixed model analyses failed to show a clinical effect of BMI on brain volume and cognitive function. Conclusion: BMI did not show an effect on cognitive function and brain volume among MS patients. Although there is increased interest in the effects of modifiable factors on the course of MS, the effects of BMI on brain volume and cognitive function are debatable and warrant further research. ClinicalTrials.gov NCT00211887